Design an in-situ reduction of Ni/C–SiO2 catalyst and new insights into pretreatment effect for CH4–CO2 reforming reaction. (20th April 2017) - Li, Hangjie; He, Yingluo; Shen, Dongming; Cheng, Shilin; Wang, Jingyan; Liu, Heyang; Xing, Chuang; Shan, Shengdao; Lu, Chengxue; Yang, Ruiqin
Abstract: A series of Ni/C–SiO2 catalysts with high Ni 0 dispersion were prepared through impregnation method with glucose as the carbon source as well as the reduction agent. During the calcination process under N2 atmosphere, the generated reductive substances, like CO, H2 and carbon derived from decomposition and carbonization of glucose, which could transform NiO into Ni 0 particles completely, according to XRD and H2 -TPR analysis. To improve the catalytic performance of CH4 –CO2 reforming reaction, the Ni/C–SiO2 catalyst was further pretreated under N2, H2 and CO2 atmosphere prior to the reaction. The CO2 pretreated catalyst exhibited excellent catalytic activity and superior stability comparing with other catalysts. A rapid deactivation occurred on the Ni/SiO2 catalyst prepared by traditional impregnation method during 10 h test. Reversely, the CO2 pretreated catalyst maintained a high CH4, CO2 and Ctotal conversion (71.1, 81.1 and 77.1%, respectively) during a 40 h time-on-stream test, which was attributed to homogenous Ni particles dispersion and strong interaction between metal and support. This methodology opens up a possibility for diversification in carbon-silica composite catalysts. The working catalyst without further reduction process will give the required metal-support interaction for the novel synthesis. Graphical abstract: We present a facile synthesis route for the direct preparation of Ni-based mesoporous carbon/silica composite catalyst without further reduction process for the CO2 reforming of CH4 reaction. The CO2 pretreated Ni catalyst exhibits high catalytic activity and superior carbon deposition resistance. Highlights: Ni-based catalysts prepared by impregnation with the addition of glucose. The as-prepared Ni/C–SiO2 catalysts realized in-situ reduction. The catalytic performance was enhanced through pretreatment with CO2, N2 and H2 . Superior catalytic performance was obtained after CO2 pretreatment.